AQUATIC EXERCISE IN PATIENTS WITH CHRONIC LOW BACK PAIN: A CASE STUDY - Wardani, Aulia Ayu Kusuma; Supriyadi, Arin; Pristianto, Arif (Academic Physiotherapy Conference Proceeding, 2021)
Introduction : Chronic low back pain is defined as pain in the lower back that lasts more than 12 weeks. The average prevalence of LBP sufferers is 39% in adults. In Lower Cross Syndrome there is tension in the thoraco-lumbar extensor muscles that cross the m. iliopsoas and m. rectus femoris. As well as weakness in the abdominal muscles that cross the m. gluteus maximus and medius. Schober test is used to determine ROM in the lumbar. Aquatic exercise can be used for the purpose of facilitating Range of Motion (ROM) exercises, facilitating weight-bearing exercises, minimizing the risk of injury or re-injury during rehabilitation, and promoting relaxation. Case Presentation : A patient named Mr. AN is 36 years old and works in the TNI. The patient complained of pain in the lower back and limitation of bending motion. Diagnosis of Chronic Low Back Pain (non-specific). Schober test measurements obtained results of 2 cm. Management and Outcomes : The physiotherapy process was carried out on patients in the hospital with 5 meetings. The aquatic exercise movements used include Stretching, Strengthening, Stabilization, Pelvic Tilt. Measurement of lumbar ROM using the Schober test. Discussion : After the patient received 4 sessions of physiotherapy, evaluation of the lumbar ROM measurement was carried out using the Schober test. The results of the measurement of lumbar ROM with the Schober test showed a significant improvement, from 2cm to 3.1cm. Where with these results it can be concluded that there is an additional lumbar ROM. Conclusion : The physiotherapy program which was carried out four times in cases of Chronic Low Back Pain using aquatic exercises which included stretching, strengthening, stabilization, and pelvic tilt was proven to be able to increase the Range of Motion (ROM) in the lumbar.